2016
DOI: 10.5194/bg-13-989-2016
|View full text |Cite
|
Sign up to set email alerts
|

The organic sea-surface microlayer in the upwelling region off the coast of Peru and potential implications for air–sea exchange processes

Abstract: Abstract. The sea-surface microlayer (SML) is at the uppermost surface of the ocean, linking the hydrosphere with the atmosphere. The presence and enrichment of organic compounds in the SML have been suggested to influence airsea gas exchange processes as well as the emission of primary organic aerosols. Here, we report on organic matter components collected from an approximately 50 µm thick SML and from the underlying water (ULW), ∼ 20 cm below the SML, in December 2012 during the SOPRAN ME-TEOR 91 cruise to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
170
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(197 citation statements)
references
References 98 publications
(102 reference statements)
27
170
0
Order By: Relevance
“…In addition, after adding the E. huxleyi seed culture, no influence of wind speed on slopes of CSP SML (2-16 µm) was detected. These results indicated that the influence of wind speed on size distribution of gel particles may be more pronounced for TEP SML than for CSP SML (Prieto et al, 2002;Engel and Galgani, 2016).…”
Section: Tep and Csp In Sml Related To Wind Speedmentioning
confidence: 87%
See 4 more Smart Citations
“…In addition, after adding the E. huxleyi seed culture, no influence of wind speed on slopes of CSP SML (2-16 µm) was detected. These results indicated that the influence of wind speed on size distribution of gel particles may be more pronounced for TEP SML than for CSP SML (Prieto et al, 2002;Engel and Galgani, 2016).…”
Section: Tep and Csp In Sml Related To Wind Speedmentioning
confidence: 87%
“…Also, proteinaceous gels and amino acids can be enriched in the SML and in sea spray aerosols (SSAs) (Kuznetsova et al, 2005). Since gel particles with fractal scaling provide a relatively large surface-to-volume ratio, they are assumed to act as barriers at the interface between air and sea, potentially reducing molecular diffusion rates (Engel and Galgani, 2016). Thus, the enrichment of organic matter, including gels, in the SML could modulate the air-sea gas exchange at low and interPublished by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations